2004
DOI: 10.1182/blood-2003-10-3485
|View full text |Cite
|
Sign up to set email alerts
|

Natural killer T cells accelerate atherogenesis in mice

Abstract: In addition, repeated injections of ␣-GalCer or the related glycolipid OCH to apolipoprotein E knockout (apoE ؊/؊ ) mice during the early phase of atherosclerosis significantly enlarged the lesion areas compared with mice injected with vehicle control. However, administering ␣-GalCer to apoE ؊/؊ mice with established lesions did not significantly increase the lesion area but considerably decreased the collagen content. Atherosclerosis development in either AD-fed WT or apoE ؊/؊ mice was associated with the pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
158
4

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 177 publications
(179 citation statements)
references
References 48 publications
17
158
4
Order By: Relevance
“…27 We have demonstrated that NKT cells may be important in the evolution of atherosclerotic lesions by communicating macrophages through cell-cell interactions and/or secreting inflammatory cytokines. 10 Some of the inflammatory processes involved in atherogenesis (as shown in our previous study) resemble adipose tissue inflammation in the present study. Therefore, NKT cells are considered to mediate chronic inflammation in vascular and adipose tissues and can represent a direct and common soil for the development of atherosclerotic cardiovascular disease and diabetes.…”
Section: Ohmura Et Al Natural Killer T Cells and Glucose Intolerancesupporting
confidence: 84%
See 1 more Smart Citation
“…27 We have demonstrated that NKT cells may be important in the evolution of atherosclerotic lesions by communicating macrophages through cell-cell interactions and/or secreting inflammatory cytokines. 10 Some of the inflammatory processes involved in atherogenesis (as shown in our previous study) resemble adipose tissue inflammation in the present study. Therefore, NKT cells are considered to mediate chronic inflammation in vascular and adipose tissues and can represent a direct and common soil for the development of atherosclerotic cardiovascular disease and diabetes.…”
Section: Ohmura Et Al Natural Killer T Cells and Glucose Intolerancesupporting
confidence: 84%
“…8 These lymphocytes are mainly CD4-positive lymphocytes that express proinflammatory T H 1 cytokines, such as IFN-␥, and orchestrate the inflammatory response in the vascular wall by activating other cells. Previous studies, 9,10 including our own studies, demonstrated that NKT cells were present in atherosclerotic lesions and are critically important in atherogenesis. These findings suggest that NKT cells can also be involved in inflammation within adipose tissue.…”
mentioning
confidence: 56%
“…Thioglycolate-elicited macrophages pulsed with oxidized LDL express elevated levels of CD1d and induce interferon-γ production by NKT cells (Nakai et al, 2004). CD8 + T cells also promote the development of atherosclerotic plaques by perforin-and granzyme B-mediated apoptosis of macrophages and tumor necrosis factor α-mediated inflammation (Kyaw et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…After 2 h, spleens were removed and single cell suspensions were prepared. Splenocytes were suspended in RPMI-1640 supplemented with 10% fetal calf serum, 100 U/ml penicillin, 100 μg/ml streptomycin and 5x10 -5 M 2-mercaptoethanol (culture medium) and cultured in 24-well plates at 5x10 6 cells/ml for 90 min (23). Culture supernatants were harvested and quantified for IL-4 and IFN-Á using mouse IL-4 and IFN-Á enzyme-linked immunosorbent assay (ELISA) sets (Biosource) according to the manufacturer's protocol.…”
Section: Methodsmentioning
confidence: 99%
“…Propidium iodide (Sigma, St. Louis, MO) positive cells were electronically gated out from the analysis. The stained cells were analyzed on a FACScalibur flow cytometer (Becton-Dickinson, Mountain View, CA) with CellQuest software as described elsewhere (23).…”
Section: Methodsmentioning
confidence: 99%